Physicochemical and antimicrobial properties of kefiran /waterborne polyurethane film incorporated with essential oils on refrigerated ostrich meat. (November 2018) - Hedayati Rad, Fatemeh; Sharifan, Anousheh; Asadi, Gholamhassan
Abstract: The evaluation of the physicochemical and antimicrobial properties of kefiran/waterborne polyurethane blend (K/WPU) film incorporated with Zataria multiflora (ZM) and Rosmarinus officinalis essential oils (RO) with concentration 5, 10, 15 and 20% (v/v) for ostrich meat packaging were the goals of this study. The band shift of the Fourier transform infrared spectra implied that intermolecular hydrogen bonding between the EOs and K/WPU film. By increasing the EOs concentration on the films thickness, elongation at break and yellowness index were increased while water vapor permeability, tensile strength, lightness and whiteness index significantly decreased (P < 0.05). Both of the EOs has significant antibacterial activity against Lactobacillus plantarum, Escherichia coli and Staphylococcus aureus ; this was proved by the agar diffusion method (P < 0.05). The total viable counts similar to all the tested bacteria were significantly inhibited by the K/WPU film containing 20% ZM and RO on ostrich meat during 12 days of storage in the refrigerator at 4 °C. ZM shows higher antimicrobial activity in comparison to RO due to the presence of terpenoid phenol compounds. Overall, these active films, especially in combination with ZM, exhibited desirable properties thus can be protected the safety and extended the shelf-life of food products. Highlights: Active K/WPU films incorporating ZEO and REO were obtained. Essential oils improved physicochemical properties of K/WPU Film. Active films reduced the microbiological growth in refrigerated ostrich meat. The antimicrobial films showed favorable characteristics as active packaging.